KEDUDUKAN FATWA DALAM KONSTRUKSI HUKUM ISLAM - Ibnu Elmi AS Pelu (INSTITUT AGAMA ISLAM NEGERI PALANGKA RAYA, 2019)
Fatwas as a result of human thought use the main legal sources, but can be categorized into ijtihad, because the process of determining fatwas is done through methods determined by the science of ushul fiqh. In judicial practice in Indonesia, fatwas can be included as legal experts' opinions. Fatwa is a legal opinion or opinion on Islamic law on considerations that can be taken from legal sources as legal considerations for judges to give decisions. Fatwas are issued by Islamic scholars or jurisprudents who are able to raise the problem of needs that require basic answers on the basis of the law about activities or activities that can be religious or non-religious in nature. Fatwa becomes one of the sessions in Islamic law to provide answers and solutions to problems raised by the people. While the Muslims at the time of the fatwa as a reference in contradiction and behavior. The position of the fatwa among the general public, is like the argument among the mujtahids (al-Fatwa fi Haqqil 'Ami kal Adillah fi Haqqil Mujtahid), that is, the placement of the fatwa in the construction of Islamic law that asks for the proposition of the mujtahid. The position of fatwa in the construction of Islamic law becomes the legal basis for an act or activity which is good in nature muamalah. The classic fatwa that was transferred (ikhtiyariah) or a choice that is not legally binding.However, associating morals with mustafti or someone who requests a fatwa. This is reinforced through the theory of acceptance of Islamic law, which is the basis of the obligation of every Muslim to approve and comply with Islamic law, the source of which is fatwa, both from philosophical, juridical, and sociological sources.